Freeze drying and calcining hydrotalcite for improving acid neutralizing capacity - Deny Puriyani Azhary; Sundani Nurono Soewandhi; Saleh Wikarsa (Indonesian Journal of Pharmacy, 2010)
Acid  neutralizing  capacity  (ANC)  is  one  of  the  important  factor  on effectivity  determination  of  antacid  dosage  forms.  Antacid dosage forms have different values depend on their ANC.  The objective of this research was to modified physical and chemical properties of hydrotalcite which can increase its acid neutralization capacity.  Hydrotalcite was treated by freeze drying and calcination at different temperature 100, 200, 300, and 500°C. This hydrotalcite was characterized by X-Ray Diffractometer  (XRD)  and  Scanning  Electron Microscope (SEM); and was determined acid neutralization capacity. The results showed  that  acid  neutralization  capacity  of  hydrotalcite  increased  after  it  was freeze  dried and  calcined  at  200,  300  and  500  °C.  The  result  of  XRD  for  the hydrotalcite  calcined  at  200  °C  have  showed  the  lower  intensity  of  peaks, whereas the calcination at 300 and 500 °C were disappeared and appeared new peaks at different 2θ.Key words: Acid neutralization capacity, hydrotalcite, calcination, XRD, SEM